(untitled) (Bangladesh Journal of Zoology, 2010)
Esterase isozyme variability was analysed in eight different tissues to distinguish between, Nile Tilapia (NT) and Genetically Improved Farmed Tilapia (GIFT), of the species Oreochromis niloticus L. The tissues were anterior, dorsal, pectoral, buccal, anal, tail, gill and heart muscles. Polyacrylamide gel electrophoresis (7.5% PAGE) was employed for this purpose and the substrate used was α napthyl acetate. Five esterase bands, namely Est-11.65, Est-21.32, Est-31.00, Est-40.73 and Est-50.38 were found to be common for both GIFT and NT in the different observed tissues. Est-60.25 was observed only in GIFT as an extra band. Esterase had tissue-specific and species-specific expression. Est-1 band was detected in anterior and dorsal muscles; Est-2 in anterior, dorsal, pectoral, gill and heart muscles; Est-3 in all tissues; Est-4 was observed in all tissues of NT except in dorsal muscle; in GIFT samples it was absent in anterior, dorsal, gill and heart tissues. Est-5 occurred in anal, dorsal, gill, heart and pectoral muscles but not in the anterior, buccal and tail samples. Esterase-6 was identified only in GIFT with a variation in intensity ranged from faint and medium to deep in the dorsal, anal and heart tissues. This band restricted only in GIFT could be used as an identification marker to distinguish between NT and GIFT. Bangladesh J. Zool. 38(1): 119-126, 2010